Energy Systems in the Era of Energy Vectors A Key to Define, Analyze and Design Energy Systems Beyond Fossil Fuels - Orecchini, Fabio; Naso, Vincenzo (Green Energy and Technology,, 2012)
What lies beyond the era of fossil fuels? While most answers focus on different primary energy resources, Energy Systems in the Era of Energy Vectors provides a completely new approach. Instead of providing a traditional consumption analysis of classical primary energy resources such as oil, coal, nuclear power and gas, Energy Systems in the Era of Energy Vectors describes and assesses energy technologies, markets and future strategies, focusing on their capacity to produce, exchange, and use energy vectors. Special attention is given to the renewable energy resources available in different areas of the world and made exploitable by the integration of energy vectors in the global energy system. Clear definitions of energy vectors and energy systems are used as the basis for a complete explanation and assessment of up-to-date, available technologies for energy resources, transport and storage systems, conversion and use. The energy vectors scheme allows the potential realisation of a worldwide sustainable energy system to fulfil global development expectations by minimising both the impact on the environment, and the international political frictions for access to limited and concentrated resources. Energy Systems in the Era of Energy Vectors is an informative read for researchers and advanced students in industrial, energy and environmental engineering. It also contains valuable information for managers and technicians working in the energy sector.